False History, False Gods: The Connection between Power and Information in Dune (1965) and City of Illusions (1967) - Inês Pastor, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: The interest in understanding how information is controlled and circulated has recently increased exponentially, mostly due to the spread of disinformation from those in power (those looking to attain it or increase it). Seemingly widespread — though by no means a recent occurrence — during the 2016 American Presidential Campaign, the reliance on disinformation to steer public opinion has also characterized, for example, the rise of far-right political parties such as Chega (Portugal) and Vox (Spain) across Europe as well as how the conflicts in Ukraine and Gaza are presented on social media. It has become, thus, mandatory to rely on fact-checking platforms but, above all, on our own critical thinking and ability to scrutinize information and its sources. As a result, it seems relevant to also analyze this subject matter in literature, as a way of attempting to obtain some insight into how to navigate and mitigate the problem. This article aims to examine how information, history and legend are weaponized by different entities to oppress those with less power in Frank Herbert’s Dune (1965) and Ursula K. Le Guin’s City of Illusions (1967), and also consider the presence, in both novels, of elements of hope and liberation from oppression through the unveiling of truth, whatever it may be. To achieve this, key and representative moments in both novels are contemplated briefly and then compared, establishing a sort of dialogue between Herbert and Le Guin’s respective imaginaria.